2017
DOI: 10.1002/pc.24571
|View full text |Cite
|
Sign up to set email alerts
|

Reliability in the characterization of fiber length distributions of injection molded long carbon fiber composites

Abstract: The mechanical properties of a discontinuous fiber reinforced composite material are dependent on the length of the reinforcing fibers. Long-fiber thermoplastic (LFT) composites offer a compromise between ease of manufacture and mechanical properties for structural applications and are conventionally made using fibers that are initially 10-14 mm long. However, fiber attrition during the injection molding process significantly reduces the final fiber lengths in molded composite and produces a fiber length distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The experimentally-based DVC analysis showed that the highest strain values were localized in the region of microvoid nucleation, which corresponded spatially to the hydrostatic stress hot-spot predicted by the finite element model. Typically, engineers are not interested in fragments of fibers with aspect ratios close to one because they contribute almost no load bearing capability when compared to their longer cylindrical neighbors present in the microstructure [28][29][30] . Therefore, techniques and algorithms to detect and characterize fibers are typically not suitable for ≤ l d / 1, which can be easily confused with noise 30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimentally-based DVC analysis showed that the highest strain values were localized in the region of microvoid nucleation, which corresponded spatially to the hydrostatic stress hot-spot predicted by the finite element model. Typically, engineers are not interested in fragments of fibers with aspect ratios close to one because they contribute almost no load bearing capability when compared to their longer cylindrical neighbors present in the microstructure [28][29][30] . Therefore, techniques and algorithms to detect and characterize fibers are typically not suitable for ≤ l d / 1, which can be easily confused with noise 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Typically, engineers are not interested in fragments of fibers with aspect ratios close to one because they contribute almost no load bearing capability when compared to their longer cylindrical neighbors present in the microstructure [28][29][30] . Therefore, techniques and algorithms to detect and characterize fibers are typically not suitable for ≤ l d / 1, which can be easily confused with noise 30,31 . In this work, the fragment of glass was manually observed in the in-situ tomography images, detected as a fragment of a fiber, included in the microstructural simulation, and proved to be a region of high hydrostatic stress and a region of corresponding microvoid nucleation, as was seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, then, is the resulting fiber breakage caused by the high shears during the manufacturing processes. Thus, the as manufactured aspect ratio is of interest and an approach similar to that of [16] will be performed. A Q50 Thermogravimetric Analyzer (TA Instruments, New Castle, DE, USA) was used to observe the decomposition of GFPP in the presence of air and nitrogen, and typical results are shown in Figure 4.…”
Section: Fiber Aspect Ratiomentioning
confidence: 99%
“…The reduction in the fiber length distribution depends on process parameters such as back pressure, speed of revolution, barrel temperature and the polymer melt shear rates [15]. In quantifying the fiber length distribution, it was shown in [16] that over 800 fiber samples, properly selected from within a sample set, are required to achieve an error less than 5%. Fiber measurements can be biased based on improper sampling on the edges of the sample area, fiber breakage during sample preparation, and improper discrimination for very short and very long fibers, the details of which are expounded upon in Section 2.2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation